PERAN LITERASI KEUANGAN DAN PEMANFAATAN FINTECH BAGI MASYARAKAT GUNA MENINGKATKAN PENDAPATAN UMKM PADA SEKTOR MAKANAN ONLINE DENGAN APLIKASI DANA - Fandiyanto, Randika; Nuzulfawati, Firda; Safitri, Sofiyana Meilani; Sakbania, Alviatus; Faidah, Selina Nur; Ramadhani, Ikhtiara Bulan; Khofilah, Siti Nur (Fakultas Ekonomi dan Bisnis, 2024)
Financial literacy is very important in the economy because it can empower MSMEs to manage their finances effectively. The use of fintech, such as the DANA application, provides benefits to the community in terms of easy access to transactions, including digital payments, business loans and better financial management. This article aims to explore how the combination of financial literacy and fintech can increase MSME income in the online food sector, focusing on the DANA application as a case study. The research methodology involves collecting qualitative descriptive data to evaluate the impact of fintech and financial literacy on MSMEs. The results of this research were created with the hope that it can share very valuable knowledge with interested and related objects in increasing support for MSMEs through increasing financial literacy and the use of fintech, especially through the DANA application.